The Rate of Adverse Events of Sodium-Glucose Cotransporter 2 Inhibitors: : A Meta-Analysis of Randomized Clinical Trials - Sajdeya, Omar (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.